(untitled) (London Journal of Engineering Research, 2025)
Purpose: The main objective of the study is to investigate the shaft plane inclination caused by bendingmoments and torsional vibrations during rotation without considering tooth friction. Methods: The law of vortex effects on gear vibrations was also considered. A four-degree-of-freedomstraight-tooth cylindrical gear dynamics model was developed based on the gyroscopic effect. ANSYSWorkbench was used to perform the model’s finite element analysis, and Simulink was used for the simulationand analysis of the model. Results: The gyroscopic effect is being investigated to determine the variation law of the intrinsic characteristicsofstraight cylindrical gears. The dynamic characteristics of straight cylindrical gears with and without gyroscopiceffects were compared, and the impact of gyroscopic effects on straight cylindrical gear systems was discussed. Conclusions: Forward and backward vortex phenomena can be observed under the influence of the gyroscopiceffect, as the intrinsic frequency increases with rotational speed. The results show that the gyroscopic effect significantly affects the translational and torsional vibrations of the master/follower wheel. It has a moresignificant impact on the torsional vibration displacement of the master wheel and the translational vibrationdisplacement of the follower wheel.